1981
DOI: 10.1177/096032718100100106
|View full text |Cite
|
Sign up to set email alerts
|

Acute Studies to Investigate the Mechanism of Action of Caffeine as a Teratogen in Mice

Abstract: 1 In Charles River CD 1 mice, a single dose of 100 mg kg-1 caffeine injected intraperitoneally on day 14 of pregnancy caused a low incidence of cleft palate in the fetuses. 2 Single oral doses of caffeine of 200 and 300 mg kg-1 but not 100 mg kg-1 on day 14, caused cleft palate in some of the fetuses, but was clearly toxic to the dams. 3 Oral doses of caffeine up to 300 mg kg-1 on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Several workers (DePasquale, Costa, Trovato & Galati, 1978;Spindel, Arnold, Cusack & Wurtman, 1980;Elmazar, McElhatton & Sullivan, 1981) have reported that administration of caffeine in high doses to rodents results in a rise in plasma corticosterone concentrations. However, the site of action of the drug within the hypothalamo-pituitary-adrenocortical ( ) axis has not been ascertained.…”
Section: Introductionmentioning
confidence: 97%
“…Several workers (DePasquale, Costa, Trovato & Galati, 1978;Spindel, Arnold, Cusack & Wurtman, 1980;Elmazar, McElhatton & Sullivan, 1981) have reported that administration of caffeine in high doses to rodents results in a rise in plasma corticosterone concentrations. However, the site of action of the drug within the hypothalamo-pituitary-adrenocortical ( ) axis has not been ascertained.…”
Section: Introductionmentioning
confidence: 97%
“…( 2 ) Endocrine Effects Three major aspects of the pharmacology and toxicology of caffeine have been investigated: (1) We observed that following the administration of teratogenic doses of caffeine t o mice there was a large increase in plasma corticosteroid levels. Because of the known action of corticosteroids to induce cleft palate in mice, we suggested that this may be a mechanism by which caffeine induced cleft palate in mice (Elmazar et al, 1981), and may also be a factor in the reduced fetal weight seen following caffeine administration to rats. One of the surprising features of the effects in mice however, was that despite the extremely high levels of corticosterone (values over l,OOOpg% was observed), induced by administration of 100mg/kg caffeine orally, the incidence of cleft palate was much less than we had observed following injections of equivalent amounts of corticosterone itself.…”
Section: Mechanisms Of Caffeine Induced Teratogenicitymentioning
confidence: 97%
“…Maternal effects: Three types of investigation have suggested that the effects are not mediated through changes in utero-placental blood flow. Studies from our own laboratory to measure uteroplacental blood flow in the mouse (Elmazar et al, 1981) showed that oral doses up to 300mg/kg had no measurable effect on placental blood flow as measured by a radio-chromium labelled mouse erythrocyte method. Secondly, studies from the NCTR (NCTR, 1981) on blood flow distribution in the rat using radio-strontium labelled microspheres, showed that there was no effect from single bolus doses of 120 and 160mg/kg caffeine given orally on cardiac output.…”
Section: Mechanisms Of Caffeine Induced Teratogenicitymentioning
confidence: 97%
“…Caffeine intake is negatively associated with gestational changes in animals, such as lower rates of fertilization and embryonic implantation, low birth and placental weight, greater number of stillbirths, increased expression of apoptotic markers and altered placental and bone formation [9,27,[40][41][42][43][44][45][46] ( Table 1).…”
Section: Caffeine and Pregnancymentioning
confidence: 99%
“…Elmazar and colleagues [42] induced caffeine consumption in albino female mice intraperitoneally and orally, and described increased circulating corticosterone and cleft palate in litters, although no detection of reduced utero-placental or placental-fetal blood flow were reported at 14 GD. Silva and colleagues [43], exposing female mice to oral doses of 0.3 g/liter of caffeine (diluted in water), suggested that caffeine exposure by mouse pups during gestation and lactation had deleterious effects on neuronal development, hyper excitable hippocampus, susceptibility to seizures and cognitive deficits that could remain even in adult life.…”
Section: Caffeine Intake During Pregnancy: What Are the Real Evidences?mentioning
confidence: 99%